Long-Term Suture Breakage After Scleral Fixation of a Modified Capsular Tension Ring with Polypropylene 10-0 Suture - Kristianslund O; Sandvik GF; Drolsum L (Clinical Ophthalmology, 2021)
Olav Kristianslund, Gunhild F Sandvik, Liv Drolsum Department of Ophthalmology, Oslo University Hospital and Institute of Clinical Medicine, University of Oslo, Oslo, NorwayCorrespondence: Olav KristianslundDepartment of Ophthalmology, Oslo University Hospital and Institute of Clinical Medicine, Mailbox 4956 Nydalen, Oslo, 0424, NorwayEmail olav.kristianslund@gmail.comAim: To investigate the long-term risk of suture breakage after implantation of a modified capsular tension ring (MCTR) fixated to the sclera with polypropylene 10– 0 suture.Methods: Retrospective case series of operations for subluxated phakic lenses in 2007– 2015 with implantation of an MCTR secured with a 10– 0 polypropylene suture as part of an intraocular lens (IOL)-capsular bag complex.Results: We identified 132 eyes (92 patients) operated on with an MCTR. Of these eyes, 26 (20%) had suture breakage requiring re-operation, while another eight eyes (6%) had suture breakage that did not require surgery. The re-operations occurred after a mean 4.8± 3.3 years. Suture breakage occurred in patients with a mean age of 34.0± 23.3, as compared to 43.2± 26.0 years for patients who did not experience this complication (p=0.36). In patients aged 40 years or younger at the time of surgery, 47% experienced suture breakage in one or both eyes, as compared to 19% in the age group 41– 69 years and 13% in the age group 70 years and older (p=0.004). Of the 132 eyes that were operated on, we registered one case (0.8%) of possible suture-related late endophthalmitis.Conclusion: The long-term risk of suture breakage was quite high after scleral fixation of the MCTR in this patient cohort, and it seems as the risk is increased with young age.Keywords: modified capsular tension ring, MCTR, Cionni capsular tension ring, suture breakage, Marfan syndrome, ectopia lentis, subluxated lens, scleral suturing